Student-Led, Research-Informed and Practice Focussed: University College Cork's Journey to Sustainability - John O'Halloran; John F Barimo; Siobhan Cusack; Sandra Irwin; Maria J Kirrane; Gerard Mullally; David Nyaluke; Julie O'Donoghue; Catherine O'Mahony; Mark Poland; Maurice Ryder (Journal of Sustainability Perspectives, 2025)
Sustainability is the defining challenge of our age. As engines of social progress, universities play a foundational role in achieving the UN Sustainable Development Goals (SDGs) and shaping a secure future. A student-led, research-informed, practice-focused approach has made University College Cork (UCC) one of the world’s most sustainable universities, consistently ranked in the UI GreenMetric top 10. Sustainability principles are central to teaching, research, outreach and operations at UCC, and are a cornerstone of organisational leadership, culture and strategy. UCC published its first Sustainability Strategy in 2016 and reports on priority initiatives annually. Researchers, including those in the UCC Futures Sustainability Institute, advance solutions to global challenges. Mapping research onto the SDGs ensures responsive priority setting for a sustainable future. An open-source SDG Toolkit supports the integration of sustainability in teaching, and a Connected Curriculum provides a framework to embed the SDGs in curricular and extra-curricular learning. UCC’s Sustainability Academy delivers bespoke industry-aligned programmes, educating future leaders to drive transformation. UCC integrates emerging sustainability practices into operations, recently adopting new approaches to the sustainability of its website and other digital spaces. This paper outlines UCC’s holistic journey to embedding sustainability through research, education and leadership, highlighting key enablers and success factors.